GREAT SILK ROAD AND CHOCH TOWNS: HISTORICAL PROGRESS (International journal of artificial intelligence, 2025)
This article analyzes the history of the cities of Chach along the Great Silk Road, their development processes, and their role in international trade and economic relations. Chach has long been an important trade and cultural center, playing a significant role in the connections between the East and the West. Based on archaeological findings and historical sources, the economic, social, and cultural development of Chach cities is examined. Additionally, the influence of various civilizations on the region and urban planning traditions are discussed.